Efficacy of anticaries medication in the primary prevention of dental caries (Эндодонтия Today, 2020)
A comprehensive clinical and laboratory study of the effectiveness of «Epsorin» in the prevention of dental caries is carried out. The effect of the tool is real and proved by statistics, which is associated with increased structural homogeneity of dental hard tissues and their resistance to aggressive factors of external and internal environment. In the application of the suspension, 0.2% and 0.3% solutions of «Epsorin» are defined fairly low rate of caries, as well as qualitative changes in the composition and properties of mixed saliva among children of school age. «Epsorin» is made from local raw materials (reindeer antlers), which determines the minimum cost and availability, which allows to use it extensively for the people living in the harsh climatic conditions in the North of Russia.